VULNERABILITY TO DEPRIVATION FROM MATERIAL AND ECONOMIC RESOURCES AND SOCIAL EXCLUSION IN CHILDREN FROM PAKHTUN CULTURE - Ullah, Asad; Shah, Mussawar (European Scientific Journal, ESJ, 2014)
What could be the exclusionary effects of limited access to materialresources and how unequal are these effects on children of different genders,religion and family types is the theme of this paper. Exclusion in childrenwas significant but negatively associated with eating fresh fruit most days,sufficient cloths, sufficient pocket money, parent‘s secure employment,savings from family income, affordability for one week holiday, affordabilityfor celebrating special occasions and affordability for toys. However, socialexclusion was positively associated with family always running out ofmoney. At multivariate level children of both genders were almost equallyexposed to social exclusion by means of their access to material/economicresources. However, non-Muslim children and children from single parentfamilies were more prone to exclusion due to their limited access to materialresources. Securing optimal employment, efficient management of familyresources, channelizing charity programs and securing children‘s dietaryneeds were suggested policy recommendations.